MODEL PENERAPAN PRINSIP GOOD GOVERNANCE DALAM PELAYANAN PERIZINAN DI KOTA PEKANBARU - administratio Department; Adianto Adianto; Mayarni Mayarni; Dadang Mashur (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2017)
ABSTRACT. Implementation of organizing good Governence, essentially demanding theinvolvement of all components of the stakeholders, both in environmental red tape aswell as in the environmental community. The essence of good governance is characterizedby this public service is good, this is in line with the essence of the policy ofdecentralization and regional autonomy which is intended to give discretion to the regionset up and take care of the local community and improve public services. This researchexamines the application of models of comprehensive principles of good governance in theservice of licensing in Kota Pekanbaru, factors that inhibit and supports the application ofgood governance in the service of licensing in Kota Pekanbaru. Results of the study foundthat the public approved the application of the principles of good governance in theservice of licensing conducted by the Agency of Integrated Services and capital investment(BPTPM) Kota Pekanbaru. Factors that hinder the application of the principles of goodgovernance in the service of the Agency's Integrated Services in licensing and Investment(BPTPM) Kota Pekanbaru is the factor of human resources and community patterns ofthought against the ministry. While the factors that support the application of theprinciples of good governance in the service of the Agency's Integrated Services inlicensing and Investment (BPTPM) Kota Pekanbaru is a factor and infrastructure, policysupport and financial support. Keywords: Good Governce, Public Service and Licensing Service